2021
DOI: 10.1186/s12870-021-03206-z
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and analysis of WRKY gene family in maize provide insights into regulatory network in response to abiotic stresses

Abstract: Background The WRKY transcription factor family plays significant roles in biotic and abiotic stress responses, which has been associated with various biological processes in higher plants. However, very little is known regarding the structure and function of WRKY genes in maize. Results In this study, a total of 140 ZmWRKY proteins encoded by 125 ZmWRKY genes were eventually identified in maize. On the basis of features of molecular structure and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 65 publications
5
44
0
Order By: Relevance
“…Compared with the previously reported by Zhang et al [ 20 ] and Hu et al [ 21 ], additional new ZmWRKY genes (12 and 9, respectively) were identified and renamed according to the chromosomal distribution, and some previously identified ZmWRKY genes (e.g., GRMZM2G103742) that had no corresponding gene models in maize v4 genome were considered obsolete; moreover, two genes (Zm00001d034475 and Zm00001d044315) identified by Hu et al [ 21 ] were not found in our result based on the same maize genome ( Table S1 ). The WRKY genes were categorized into three groups based on conserved domains and phylogenetic analysis, and the results were consistent with previous findings [ 21 ]. The molecular weights and isoelectric points of the ZmWRKY proteins showed a great deal of variation, likely due to their differing roles across a range of environments.…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations
“…Compared with the previously reported by Zhang et al [ 20 ] and Hu et al [ 21 ], additional new ZmWRKY genes (12 and 9, respectively) were identified and renamed according to the chromosomal distribution, and some previously identified ZmWRKY genes (e.g., GRMZM2G103742) that had no corresponding gene models in maize v4 genome were considered obsolete; moreover, two genes (Zm00001d034475 and Zm00001d044315) identified by Hu et al [ 21 ] were not found in our result based on the same maize genome ( Table S1 ). The WRKY genes were categorized into three groups based on conserved domains and phylogenetic analysis, and the results were consistent with previous findings [ 21 ]. The molecular weights and isoelectric points of the ZmWRKY proteins showed a great deal of variation, likely due to their differing roles across a range of environments.…”
Section: Discussionmentioning
confidence: 48%
“…In this study, a total of 128 putative non-redundant WRKY genes were identified and characterized using the new maize reference genome, the number of WRKY genes is higher than that identified in the previous studies [ 20 , 21 ]. Compared with the previously reported by Zhang et al [ 20 ] and Hu et al [ 21 ], additional new ZmWRKY genes (12 and 9, respectively) were identified and renamed according to the chromosomal distribution, and some previously identified ZmWRKY genes (e.g., GRMZM2G103742) that had no corresponding gene models in maize v4 genome were considered obsolete; moreover, two genes (Zm00001d034475 and Zm00001d044315) identified by Hu et al [ 21 ] were not found in our result based on the same maize genome ( Table S1 ). The WRKY genes were categorized into three groups based on conserved domains and phylogenetic analysis, and the results were consistent with previous findings [ 21 ].…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In-depth analysis of the structural characteristics of introns and exons is a key step in the process of gene family evolution [ 60 , 61 ]. A varied number of introns was possessed by AtruWRKY genes, group Ⅰ had more introns in this study, implying that the molecular structure in the group Ⅰ of WRKY genes may be quite conserved in the process of evolution, which conductive to the protein diversity caused evolution [ 62 , 63 ]. It seems that the crucial function of the WRKY gene family in A. truncatum is very much related to group Ⅰ, and similar results were found in eggplant ( Solanum torvum L.) [ 60 ].…”
Section: Discussionmentioning
confidence: 99%